The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.surg.2009.09.028
|View full text |Cite
|
Sign up to set email alerts
|

A novel HSP90 modulator with selective activity against thyroid cancers in vitro

Abstract: Background-HSP90 is a chaperone protein regulating several client proteins involved in thyroid cancer development. The purpose of this study is to mechanisticially evaluate a novel natural-product HSP90 inhibitor in thyroid cancer cell lines for future translational applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
(17 reference statements)
1
18
0
Order By: Relevance
“…The first Solanaceae species we investigated was the Latin American spiny shrub V. breviflora , where cytotoxicity-guided purification led to the isolation and characterization of withaferin A ( 1 ) (Samadi et al 2009; Samadi et al 2010). Preliminary results revealed 1 as a promising chemotherapeutic candidate for antitumor therapy, and that further translational evaluation of 1 was warranted (Grogan et al 2013; Samadi et al 2012).…”
Section: Withanolides Isolated From Natural Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first Solanaceae species we investigated was the Latin American spiny shrub V. breviflora , where cytotoxicity-guided purification led to the isolation and characterization of withaferin A ( 1 ) (Samadi et al 2009; Samadi et al 2010). Preliminary results revealed 1 as a promising chemotherapeutic candidate for antitumor therapy, and that further translational evaluation of 1 was warranted (Grogan et al 2013; Samadi et al 2012).…”
Section: Withanolides Isolated From Natural Sourcesmentioning
confidence: 99%
“…Furthermore, mechanistic studies showed that 1 inhibits proliferation by inducing a dose-dependent G2/M cell cycle arrest while promoting cell death through both intrinsic and extrinsic apoptotic pathways (Grogan et al 2013; Samadi et al 2009; Samadi et al 2010; Samadi et al 2012). …”
Section: Antiproliferative Evaluation Of Withanolide Librarymentioning
confidence: 99%
“…These compounds also affect cell-cycle arrest, with significant shift of cells into G2/M arrest, as reported with WA. 21 …”
Section: Discussionmentioning
confidence: 99%
“…This drug compound, Withaferin A, has been shown to inhibit human MTC cell proliferation (TT cells and DRO81-1) in vitro by MTS assay and confirmed by trypan-blue exclusion assay 18. This inhibition occurred at a higher potency than drugs like 17-AAG, a popular heat shock protein 90 inhibitor that is currently in phase 1/2 clinical trials in patients including MTC patients.…”
Section: Introductionmentioning
confidence: 88%